Tribological Characterization of Al-bronzes Used as Mold Materials - Atapek Ş. H.; Çelik G. Aktaş; Polat Ş.; Pisarek B. (Archives of Foundry Engineering, 2017)
Among the copper based alloys, Cu-Al-X bronzes are commonly used as mold materials due to their superior physical and chemical properties. Mold materials suffer from both wear and corrosion, thus, it is necessary to know which one of the competitive phenomenon is dominant during the service conditions. In this study, tribo-corrosion behavior of CuAl10Ni5Fe4 and CuAl14Fe4Mn2Co alloys were studied and electrochemical measurements were carried out using three electrode system in 3.5 % NaCl solution in order to evaluate their corrosion resistance. In tribo-corrosion tests, alloys were tested against zirconia ball in 3.5 % NaCl solution, under 10N load with 0.04 m/s sliding speed during 300 and 600 m. The results indicate that (i) CuAl10Ni5Fe4 alloy is more resistant to NaCl solution compared to CuAl14Fe4Mn2Co alloy that has major galvanic cells within its matrix, (ii) although CuAl10Ni5Fe4 alloy has lower coefficient of friction value, it suffers from wear under dry sliding conditions, (iii) as the sliding distance increases, corrosion products on CuAl14Fe4Mn2Co surface increase at a higher rate compared to CuAl10Ni5Fe4 leading to a decrease in volume loss due to the lubricant effect of copper oxides.